Lectotypification of four names in Andrographis (Acanthaceae) - Gnanasekaran, Gunadayalan; Murthy, Garimella Venkata Suryanarayana (Phytotaxa, 2015)
The genus Andrographis Wallich ex Nees von Esenbeck (1832: 116) is represented by 28 taxa in India (Karthikeyan et al. 2009), and distributed mainly in the southern region with 23 taxa endemic to the country (Gnanasekaran & Murthy 2012). During the present study on the systematics of Andrographis in India, a total of six names has already been lectotypified (Gnanasekaran & Murthy 2012, 2014, 2015, Gnanasekaran et al. 2014). In the present communication, the following four names, A. explicata (Clarke 1884: 504) Gamble (1924: 1049), A. lobelioides (Wallich ex Nees von Esenbeck 1832: 115) Wight (1850a: 191, t. 164-b [f. 11]), A. neesiana Wight (1850b: 8, t. 1561) and A. paniculata (Burman 1768: 9) Wallich ex Nees von Esenbeck (1832: 116) are lectotypified here to avoid any ambiguity in the application of these names. Lectotypes are selected after a thorough scrutiny of protologues, syntypes and in accordance with articles 9.2, and 9.14 and recommendation 9C.1 of ICN (McNeill et al. 2012). Digital images of designated specimens (Figs. 1–4) are provided.